ASSESSMENT OF DEMOGRAPHIC AND CLINICAL PROFILE OF DRUG-SENSITIVE AND MULTIDRUG-RESISTANCE PULMONARY TUBERCULOSIS PATIENTS IN NORTHERN INDIA (International Journal of Food and Nutritional Sciences, 2022)
Our study aimed to characterize culture-positive multidrug-resistant tuberculosis (MDR-TB) patients from a center specializing in drug-resistant tuberculosis (DR-TB) in India. We initially performed research on 436 patients and later on we selected 395 patients as subject which was decided on the basis of particular criteria of inclusion and exclusion of subjects. Descriptive statistics were then utilized to analyze the social demographics, clinical features, and associated risk factors among culture-positive TB patients. The mean age of the patients included in our study was 43.6 years, with a majority of 61.5% being males. Notably, 27.3% of patients were smokers, 6.6% of the subject were found to be ex-smokers, and the remaining 66.1% were found to be non-smokers. The most commonly reported symptom among these patients was cough with expectoration, noted in 92.4% of cases, followed by complaints of fever which is 78%, haemoptysis which is 30%, and weight loss which is 63%. Additionally, 21% of the population had a family history of TB, highlighting a potential genetic predisposition. Comorbidities were prevalent among the study population, with 23.8% of patients presenting with other medical conditions. Among these, diabetes was the most common comorbidity, affecting 37 individuals. Regarding TB diagnosis, out of the 395 cases analyzed, 125 were identified as drug-sensitive pulmonary tuberculosis, while the remaining 270 subjects were categorised as MDR-TB. Smear grading revealed that 204 cases showed 2+ or 3+ positivity, while 191 cases exhibited 1+ or scanty positivity. Further analysis of culture-positive samples (364 in total) through drug susceptibility testing (DST) revealed significant resistance patterns. Specifically, 251 cases were resistant to rifampicin (RIF), 243 to isoniazid (INH), and 247 to ethambutol (EMB). Our findings highlight a substantial number of MDR-TB cases in the studied population, largely attributed to poor adherence to anti-TB medications. Consequently, we emphasize the importance of interventions such as reducing alcohol intake, enhancing education, promoting TB advocacy and communication, increasing testing and notification efforts, and implementing comprehensive TB control programs to effectively combat this public health challenge.